State Laws and Child Custody Recommendations in Cases of Intimate Partner Violence, 2009-2010 (United States) - Saunders, Daniel ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study was a secondary analysis of Custody Evaluators' Beliefs about Domestic Abuse Allegations, 2009-2010 [United States] (ICPSR 30962 - https://doi.org/10.3886/ICPSR30962.v1). The purpose of this study was to conduct further analysis of a recent, National Institute of Justice (NIJ) sponsored national survey of professionals to better understand the relationship between family law statutes and professionals' recommendations for child custody and visitation in cases of intimate partner violence. The samples involve 512 child custody evaluators and 200 judges from 46 states. Evaluators and judges responded to a case vignette of serious intimate partner violence (IPV). They indicated recommendations they would make for custody and visitation and the perceived risk of future harm. Evaluators also reported on their history of actual recommendations in IPV cases. The original study investigated beliefs about custody, value-laden beliefs, knowledge professionals had acquired on IPV, the number of survivors they had known, and their work setting, education, and other demographics. In the current study, statutory provisions with sufficient sample sizes of professionals with and without the provisions were used in the analysis.